Combustion of Ammonia Mixed with Dimethyl Ether - Ruiz Gutiérrez, Adrián; Alzueta Ania, María Ujué; Rebollo Marco, Paloma (Jornada de Jóvenes Investigadores del I3A, 2023)
In view of the problems caused by conventional means of energy, it is necessary to promote cleaner and more environmentally friendly ways to produce energy. Therefore, the study of ammonia combustion can be providential for the progressive substitution of more conventional combustion fuels such as oil or natural gas.